The importance and usefulness of corporate annual reports in Malaysia - Mohd Ghazali, Nazli Anum (Universitas Gadjah Mada, 2010)
The purpose of this study is to examine the perceived importance and usefulness of corporate annual reports in Malaysia and to determine if there is a difference between the perceptions of preparers and users of corporate annual reports. Data for this study were collected using a questionnaire survey conducted in late 2006 and early 2007. Preparers are represented by chief financial officers while users by investment analysts. The mean scores for preparers and users are compared using the independent samples t test and the non-parametric Mann-Whitney test to determine if there are any statistically significant differences in their opinions. The findings reveal that preparers rank the annual report as the most important source of corporate information. Users, on the other hand, rank the annual report as the second most important after the visits to companies. However, the difference in the mean scores of preparers and those of users on the importance of annual reports is not significant at 5 percent level. The difference in the mean scores for the visits to companies is, on the other hand, statistically significant at 5 percent level. An implication for this finding is whether the annual report serves the information needs of analysts for decision-making purposes. An opportunity thus arises for future research to examine information needs of analysts and if there is a gap between information provided in annual reports and that required by analysts.